Does bureaucracy lead to economic development in ASEAN?. (10th May 2019) - Khusaini, Mohamad
Bureaucracy issue is a challenge to the economic management of the countries in the world. In many studies, bureaucracy can affect a country's economic development. Inefficient bureaucracy will create a high cost economy and decrease investment in which eventually it may obstruct the economic growth. This research aims at analysing the effect of bureaucracy, investment, and government spending on the economic development. By using multiple regression analysis with Fixed Effect Model, the results indicate that investment and government spending have positive effect on the gross domestic product (GDP), while the index of bureaucracy shows varying results in affecting GDP.